Exosomes in cardiovascular diseases : biomarkers, pathological and therapeutic effects - Xiao, Junjie; Cretoiu, Sanda (Springer, 2017)
The book provides and intensive overview on exosomes in cardiovascular diseases, its potential as biomarkers, as well as pathological and therapeutic effects. It firstly describes the general aspects of exosomes including the definition, formation and secretion of exosomes and highlight their roles as biomarkers and pathological and therapeutic effects in cardiovascular diseases as well. Secondly, basic aspects of exosomes including the purification methods of exosomes, exosomes content, and functional roles of the cardiovascular exosomes are summarized. Thirdly, exosomes as biomarkers of cardiovascular diseases are overviewed including their roles in diagnosis, prognosis and reaction to therapy. Fourthly, pathological effects of exosomes and therapeutic effects of exosomes are highlighted. Finally, future prospects of exosomes in cardiovascular research would be provided. This is an essential reference for researchers working in cell biology and regeneration, as well as clinicians such as cardiologist"--Publisher's description.
Keywords: Cardiovascular system -- Diseases -- Molecular aspects.; Cardiovascular system -- Pathophysiology.; Biochemical markers.; elektronické knihy; electronic books